(untitled) (Journal of Architectural Design, 2022)
In the article, the topic of the design code is studied and an opinion is discussed about the projects that are expected to be implemented. At present, much attention is being paid to tourism, and the original appearance of buildings in urban areas is being lost, and advertising and information are taking over, and meaningless information is taking the place of historicity.